2022
DOI: 10.1039/d2nj03125f
|View full text |Cite
|
Sign up to set email alerts
|

Relying on the non-radical degradation of oxytetracycline by peroxymonosulfate activated with a magnetic Cu/Fe composite: performance and mechanism

Abstract: Oxytetracycline (OTC) is a typical antibiotic that poses a serious threat to the environment. However, traditional treatment methods suffer from low treatment efficiency and potential secondary contamination. Therefore, there is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The existence of CO 3 2showed a similar effect as the existence of HCO 3 because they were converted to each other (Eq. ( 8)) [42]. Obviously, microplastics showed no effect on the degradation process, which demonstrated that the Fe 3 O 4 @CR/PS had a potential for OTC degradation in the presence of microplastics.…”
Section: •-mentioning
confidence: 93%
“…The existence of CO 3 2showed a similar effect as the existence of HCO 3 because they were converted to each other (Eq. ( 8)) [42]. Obviously, microplastics showed no effect on the degradation process, which demonstrated that the Fe 3 O 4 @CR/PS had a potential for OTC degradation in the presence of microplastics.…”
Section: •-mentioning
confidence: 93%